Attributes of Rajarshi leadership: learning from Ramayana - Dinesh Kumar; Divyanshu Singh; Kritika Kritika; Narinder Kumar Bhasin (Cogent Business & Management, 2024)
AbstractIn terms of the Global Hunger Index, the ranking of India slipped to 101 in 2021 from its 94th position in 2020. The number of billionaires increased to 1007 and the number of millionaires increased by 63% but household incomes of 97% population declined during the Covid-19 pandemic. Even after the pandemic effect, the gap between rich and poor continues to widen fast. The question arises, do leadership theories in focus today have shown the right path? Necessity has arisen to revisit the leadership style followed by Corporates and Political masters and assimilate the Indian culture of ‘Vasudhaiv Kutumbkam’ to develop a comprehensive approach of spiritual transformation where leaders strive to search for a ‘Higher-order purpose of existence’ (HOPE) and embrace for a society centric approach. An understanding is being germinated to give prominence to the Indian culture emanating from scriptures like Bhagwad Gita, Ramayana, etc. It embarks on creating a value-based leadership framework that deals with a higher vision and mission and Rajarshi leadership is among such leadership. This paper is a modest attempt to trace the attributes of Rajarshi leadership in the light of the story of Ramayana wherein Rama (a prince of Ayodhaya in exile) instead of adopting short-cuts or taking the help of Ayodhya to get his wife free, made tie-up with Sugriva (a depressed and coward king hiding in the forest) and prepared an army of monkeys, nomads and downtrodden people of the forest and defeated the powerful well-equipped army of Ravana and established Rama-Rajaya.